Relationship Between Parenting Patterns and the Incidence of Stunting in Toddlers - Khaira, Nuswatul; Faisal, T. Iskandar; Kurniawan, Rahmat; Helmi, Alfian; Asmawati, Asmawati; Halimatussakdiah, Halimatussakdiah; Muchtar, Afdhal; Jamni, Teuku (Journal Keperawatan, 2025)
Background: Stunting remains a public health problem in Indonesia, including in Palu City, Central Sulawesi, with prevalence increasing from 23.9% to 24.7% in 2022, remaining below the national target for stunting reduction. Several studies have shown that 22.9% of parents practice poor parenting practices, a factor contributing to the high incidence of stunting in toddlers. Purpose: To determine the relationship between parenting patterns and the incidence of stunting in toddlers in the work area of ​​Tawaeli Health Center, Palu City. Methods: This type of research is quantitative with a cross-sectional design. The study population was all toddlers aged 24–59 months in the Tawaeli Community Health Center working area. A sample of 70 respondents was selected using a purposive sampling technique, with the inclusion criteria being toddlers who had complete data regarding height and weight and mothers who were willing to be respondents. Data on family parenting patterns were collected using a structured questionnaire, while stunting status was determined based on anthropometric data. Data analysis was performed using the Chi-Square test. Results: There was a significant relationship between family parenting patterns and the incidence of stunting in toddlers with a p value of 0.02 (p <0.05). Toddlers raised with poor parenting patterns had a higher risk of stunting than toddlers raised with good parenting patterns. Conclusion: Family parenting patterns are significantly associated with stunting in toddlers aged 24–59 months. Strengthening the family's role through education on appropriate parenting patterns needs to be a focus of pediatric and community nursing interventions in stunting prevention efforts.